Burnout - Eftimie, Mihaela (New Trends in Psychology, 2023)
Burnout syndrome is the result of chronic stress or improperly managed stress, being characterized by the onset of exhaustion and decreased performance. Some people may be at increased risk of suffering from this syndrome due to genetic predispositions or difficult moments in life (trauma, divorce, death). The stages a person goes through until he reaches exhaustion are: the strong need for affirmation, neglect of personal needs, the emergence of conflict situations either at home or at the office, denial of problems, isolation from family and social group, change in behavior, self-devaluation, feeling of inner emptiness, depressive states, physical and emotional collapse. Lack of boundaries between work and free time (private life). Our culture makes it difficult to separate work from everything else. However, it is the inability to disconnect that causes daily stressors to combine and become exhausting. Stress is the result of a temporary tension, while burnout is a continuous, permanent tension. Burnout can be considered the final stage of a break in adaptation, which results from a longterm imbalance between demands and resources, thus from a prolonged professional stress. The prevention and treatment of burnout syndrome are done using special employee assistance programs, stress management trainings and specific interventions that address the specific situations of each individual case.